Information technologies and mathematical modelling : queueing theory and applications : 15th International Scientific Conference, ITMM 2016, named after A.F. Terpugov, Katun, Russia, September 12-16, 2016. Proceedings /: queueing theory and applications : 15th International Scientific Conference, ITMM 2016, named after A.F. Terpugov, Katun, Russia, September 12-16, 2016. Proceedings. (2016) - Unknown
No abstract available